2016
DOI: 10.25011/cim.v39i5.27149
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Fibroblast Growth Factor-23 Level and Paraoxonase-1 Lactonase Activity in Chronic Hemodialysis Patients: Their Impact on the Incidence of Native AV Fistula Thrombosis

Abstract: Purpose: Thrombosis of native arteriovenous (AV) fistula is an important cause of complications in hemodialysis (HD) patients. The purpose of this study was to investigate the usefulness of measuring circulating fibroblast growth factor-23 (FGF-23) level and paraoxonase-1 (PON1) lactonase activity as potential predictors of native AV fistula thrombosis in chronic HD patients.Methods: This study included 83 HD patients (48 with thrombosed and 35 with non-thrombosed native AV fistulas) and 38 healthy volunteers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The results demonstrated that PON1 lactonase activity was significantly decreased, whereas FGF-23 was significantly elevated in HD patients with thrombosed AV fistula compared with those with non-thrombosed AV fistula. The significant negative correlation between PON1 lactonase and FGF-23, which represents a central regulator of vascular dysfunction in CKD [ 98 ], may support the suggestion that FGF-23 and PON1 lactonase values may contribute to the prediction of native AV fistula thrombosis in HD patients [ 97 ]. In a longitudinal study with CKD patients followed- up for 3 years, it was shown that the PON1 Q192R gene variant is implicated in left ventricular (LV) hypertrophy and in LV dysfunction [ 59 ], which are surrogate indicators of CVD.…”
Section: Pon1 Activity and Cardiovascular Risk In Chronic Kidney Diseasementioning
confidence: 92%
See 1 more Smart Citation
“…The results demonstrated that PON1 lactonase activity was significantly decreased, whereas FGF-23 was significantly elevated in HD patients with thrombosed AV fistula compared with those with non-thrombosed AV fistula. The significant negative correlation between PON1 lactonase and FGF-23, which represents a central regulator of vascular dysfunction in CKD [ 98 ], may support the suggestion that FGF-23 and PON1 lactonase values may contribute to the prediction of native AV fistula thrombosis in HD patients [ 97 ]. In a longitudinal study with CKD patients followed- up for 3 years, it was shown that the PON1 Q192R gene variant is implicated in left ventricular (LV) hypertrophy and in LV dysfunction [ 59 ], which are surrogate indicators of CVD.…”
Section: Pon1 Activity and Cardiovascular Risk In Chronic Kidney Diseasementioning
confidence: 92%
“…The possible associations of PON1 lactonase activity and circulating fibroblast growth factor 23 (FGF-23) levels with the incidence of native arteriovenous (AV) fistula thrombosis were examined in chronic HD patients, as AV thrombosis accounts for a great percentage of vascular access loss, developing in venous segment of native AV fistula or AV graft [ 97 ]. The results demonstrated that PON1 lactonase activity was significantly decreased, whereas FGF-23 was significantly elevated in HD patients with thrombosed AV fistula compared with those with non-thrombosed AV fistula.…”
Section: Pon1 Activity and Cardiovascular Risk In Chronic Kidney Diseasementioning
confidence: 99%